INVESTIGATION OF THE EFFECTS OF CONNECTIVE TISSUE MOBILISATION ON QUALITY OF LIFE AND EMOTIONAL STATUS IN HEALTHY SUBJECTS - Kavlak, Erdogan; Büker, Nihal; Altug, Filiz; Kitis, Ali (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Connective Tissue Massage (CTM) or Manipulation is a bodywork technique which lies at the interface between alternative approaches. The autonomic balancing responses to CTM can be useful in the treatment of anxiety. Aim: This study was planned to investigate the effects of connective tissue mobilization (CTM) on quality of life and emotional status in healthy subjects. Design; Prospective trial, Setting; Treatment and Population. The study was conducted on 100 volunteers (students). Students in second class were in CTM group (20,49±1,37 years) and students (19,50±1,15 years) educating in class 1 were in control group. Methods: Participants were assessed before and after CTM according to flexibility of trunk flexion, hamstring muscles, trunk hyperextension and lateral flexion. It was used The SF-36 Health-Related Quality of Life Inventory (SF-36) to assess general health status and Beck Depression Scale was used for assessing emotional status. Results: It was observed a significant increase at lateral flexion to the right of trunk (p=0,03) in CTM group after application. It was found a significant difference (p=0,009) in emotional status between groups. It was found differences at general health level (p=0,001), limitations in emotional role (p=0,016) in SF-36. It was some differences in depression status and some subscales of SF-36 (general health, social status, emotional well-being, pain and energy levels) in favour of control group before application. It was no difference between groups after application. Conclusion: CTM could be used for minimizing depressive symptoms, improving quality of life in healthy young subjects.